La rumba terapia y la conservación de motricidad gruesa en adultos mayores Juanas de Oro - Villa Mayorga, Kimberlly Monsserth (2022)
The following research was carried out on a global problem that has affected many sectors but especially in health care, not only because of infections but also because of a sedentary lifestyle that has increased due to the internment of individuals in their homes, moreover, the elderly, who are part of a vulnerable sector that physically, due to their age, were already limited in their physical activity, resulting in a higher deterioration of their physical systems for that reason, the objective of this research is to establish the benefits of promoting and practicing activities such as rumba therapy to improve the gross motor skills of older people. The target audience is public and private organizations that seek collective wellbeing and that also have the obligation to create public policies that promote physical activity in areas of priority attention such as the elderly, which is based on an issue of public interest, so in this way, they can reactivate themselves with physical training and also contemplate a principle of aging and dignity, where everyone as a community can contribute. In order to meet the objectives of the analysis, methodological tools were used with a quantitative, quasi-experimental, descriptive-explanatory approach, after sampling the population of older men and women between 65 and 80 years old in the parish of Atahualpa in the canton of Ambato, province of Tungurahua, the results will be reflected through the collection of data after a descriptive test. The main results obtained were the determination of the benefits of rumba therapy as a physical activity in the elderly who are capable of strengthening and preserving gross motor skills, making them feel that they are still capable, important, and strong individuals, these activities should be encouraged by all those who compose civil society and those bodies that have the competence to create programs to promote physical activity, not only by creating spaces, but also with the proper follow-up to ensure that these activities are fully performed as part of social development.